Apakah Membiarkan Anak Mengatur Asupan Makan Sendiri Dapat Menyebabkan Kegemukan? Sebuah Penelitian Case Control - Wulan Tri Yutanti; M. Jufrie; I Made Alit Gunawan; A Fahmy A Tsani (JURNAL NUTRISIA, 2016)
Background : Child control or maternal who are allowing preschool children to self-regulate their own food intakewould affect dietary intake and weight status.Children (>3 years old) tend to eat more when served larger portions and do not regulate intake as well, especially if at higher risk of obesity.Objective : To investigation child control as a risk factors on the risk of obesity and identified the association child control with dietary intake and weight in preschool children in Yogyakarta City. Method : A case control study of preschool children (aged 3 – 5) and their mother was recruited from June to October 2015. Anthropometric measurements included weight and height . Subject divided into normal weight (n=101) and overweight/obesity (n=101) group based on World Health Organization 2005 weight-for-height and were matched by gender and age, Comprehension Feeding Practices Questionnaire (CFPQ) to asses maternal feeding practices, semi quantitative food-frequency questionnaire over the past 3 months to asses children’s dietary intake.Statistical analysis was performed with Mc Nemar test and Spearman. Results : Child control variable wasnot significantly related to risk of obesity (OR = 1,18; 95%CI 0,64 – 2,19) and there is no association between child control with dietary intake and weight (p > 0,05) in preschool children. Conclusions : Child control variable wasnot significantly related to risk of obesity and there is no association between child control with dietary intake and weight in preshool children. Key Words : overweight, obesity, child control feeding practices, dietary intake, preschool children